Hospedeiros domésticos, peridomiciliares e silvestres na transmissão de Trypanosoma cruzi pelo Triatoma brasiliensis em área de caatinga no município de Tauá – CE - Bezerra, Claudia Mendonça (2013)
Traditionally, the control of human transmission of Trypanosoma cruzi is accomplished by the application of insecticides with residual action. However, knowledge about the role of hosts domestic and wild outdoor environments are critical for determining the maintenance and / or dispersion of T. cruzi. This study aimed to characterize the importance of domestic reservoirs, wild and peridomestic transmission of T. cruzi in the rural municipality of Taua (EC), inserted in Caatinga area, with emphasis on environments colonized by Triatoma brasiliensis. Among the animals household and neighbors were considered dogs, cats, pigs, goats and sheep 83 housing units (DUs). In the wild capture and examination was performed on small mammals at three sites with different degrees of antropofização, and also the capture of insects. The survey of domiciliary infestation by triatomines was performed in 251 DUs. Direct parasitological examinations were performed in insects and mammals, animals in serologic household and neighbors, Multiplex PCR on wild reservoirs and research of wild food source for insects. The proportion of infection of pigs was 6% (2/34), ovine 1% (1/102), cats 2.4% (1/41) dogs 38% (20/53). We captured nine species among rodents and marsupials. The Trichomys laurentius, with 74% (83/112), was the most abundant and widely distributed in the wild, followed by rock Kerodon 10% (11/112) and Didelphis albiventris 3.5% (4/112). 749 triatomines were captured in the household survey, with 369 (49.3%) of T. brasiliensis and 377 (50.3%) of Triatoma pseudomaculata. Only specimens of T. brasiliensis were infected with T. cruzi (25, 12.8%). Of these 3 (5.9%) were inside the home and 22 (14%) outside the home. Of the 166 triatomines captured, 132 (79%) were nymphs and other 35 (21%) adults. These, a fifth instar nymph and one male were infected with T. cruzi. The T. brasiliensis sharing the natural environment with T. laurentius, K. rock, D. albiventris, M. domestica, G. spixii, W. pyrrhorinos, C. and M. semistriatus musculus (captured animals) and G. spixii, K. cave, T. oreadicus and T. merianae (identified via food source), and animals observed during the catch (Athene cuniculariae and Felis catus) and confirmed via food source (C. hircus and G. gallus). The movement of the T. cruzi between sylvatic, peridomestic household in mammals and insects emphasizes the possibility of cases of Chagas disease in the studied region, as well as the difficulty and real necessity for its control in semi-arid areas in Northeast Brazil.